Risk perceptions on social networking sites : an investigation of age and other factors - Keaney, Aideen M. (Trinity College (Dublin, Ireland). School of Computer Science & Statistics, 2012)
Since the mid 2000’s, social networking sites (SNSs) such as Facebook and Bebo have seen phenomenal growth. These sites provide many benefits for users, but there are risks in using them. To date most of the studies that have examined the risks associated with SNSs have examined their prevalence and impact on adolescents and to lesser extent emerging adults as these age groups have been seen as the primary users of SNSs. However, recent evidence shows that the growth in the numbers using SNSs is not only continuing, but is happening in the older age groups. As far as it is known, this is the first study of its kind to examine risk prevalence on SNSs across a number of age groups, including adults. It is also the first study to examine users’ perception of these risks. The following is a summary of the methods used and the major findings of this dissertation. The research approach combines quantitative and qualitative research methods, using a mixed method sequential explanatory design. The quantitative first phase of the design is a survey of 551 adolescents (ages 12-17), 1,044 emerging adults (ages 18-25) and 156 working adults. The survey measures users’ risks perceptions with respect to SNSs. The second, qualitative phase expands on the results found in the survey and looks for explanations as to why certain risk perceptions exist. The second phase consists of 15 semi-structured interviews with the emerging adult cohort and four focus groups interviews with the adolescent group. The findings from this research in some cases confirm those found in other studies and in a number of instances contradict those found in previous work. This study also makes a number of new findings about risk perception and SNSs. While all users show an awareness and a recognition of the risks on SNSs, most users exhibit a lack of concern about the risks on SNSs and do not think that these negative events are likely to happen to them. While it might be expected that users would be most concerned and have highest risk perceptions for the serious threatening risks such as cyberbullying and meeting strangers, this is not the case and users express higher levels of concern about and perceive greater threats from risks to their reputation. For most of the negative events on SNSs, when compared to the other age groups, adolescents perceive themselves to be at a higher risk, show higher levels of awareness, are more concerned and perceive the consequences of risks to be higher. The qualitative interviews and focus group discussions highlight some misconceptions with regard to these risks and in particular users’ lack of awareness of the scale and scope of the audience on SNSs and how easily their personal information can be accessed and harvested. This research examines why some users perceive themselves to be at high personal risk on SNSs and others do not. Three factors are significant predictors of the likelihood of high personal risk perceptions: prior experience of the risk, concern about the risk and age group. The most significant predictor of high personal risk perception is prior experience. Although suggested as significant predictors of risk perception by previous research, both knowledge of risk and controllability of risk show small effects on the likelihood of high personal risk perceptions. Again, contrary to the findings of previous risk perception studies, gender does not emerge as a significant predictor for any of the risk categories. This study highlights a number of behaviours on SNSs that could make users more vulnerable to risk. Users tend to underestimate the amount of time they spend on SNSs and may be unaware of the distracting aspects of SNSs. In contrast to some previous studies, this study has found that the majority of respondents have restricted their privacy settings, indicating that SNS users may be becoming more aware and concerned about the privacy risks on SNSs. However, similar to the findings of other studies, this concern does not extend to restricting the amount of information respondents disclose. Users continue to reveal substantial amounts of personal information. Adolescents are less likely than the other age cohorts studied to reveal personal contact information, but overall older adolescents and emerging adults reveal significantly more information than the other age cohorts studied. The qualitative interviews indicate that SNS users tend to be guided by the SNS company, accepting the default privacy settings and filling in the information categories provided on the SNS. To date, most studies have addressed the prevalence of these risks for children and adolescents. This study differs as it examines the prevalence of risks over a number of age cohorts and highlights that many of these risks have been experienced by emerging adults and adults. This study addresses a number of gaps in the extant literature and the research findings provide both a theoretical and a practical contribution to this field. The results of the research include a preliminary framework that captures the factors that influence risk perception on SNSs. The findings of this research can inform not only further studies of SNS risks, but also studies of other Internet and technology related risks. Since the mid 2000’s, social networking sites (SNSs) such as Facebook and Bebo have seen phenomenal growth. These sites provide many benefits for users, but there are risks in using them. To date most of the studies that have examined the risks associated with SNSs have examined their prevalence and impact on adolescents and to lesser extent emerging adults as these age groups have been seen as the primary users of SNSs. However, recent evidence shows that the growth in the numbers using SNSs is not only continuing, but is happening in the older age groups. As far as it is known, this is the first study of its kind to examine risk prevalence on SNSs across a number of age groups, including adults. It is also the first study to examine users’ perception of these risks. The following is a summary of the methods used and the major findings of this dissertation. The research approach combines quantitative and qualitative research methods, using a mixed method sequential explanatory design. The quantitative first phase of the design is a survey of 551 adolescents (ages 12-17), 1,044 emerging adults (ages 18-25) and 156 working adults. The survey measures users’ risks perceptions with respect to SNSs. The second, qualitative phase expands on the results found in the survey and looks for explanations as to why certain risk perceptions exist. The second phase consists of 15 semi-structured interviews with the emerging adult cohort and four focus groups interviews with the adolescent group. The findings from this research in some cases confirm those found in other studies and in a number of instances contradict those found in previous work. This study also makes a number of new findings about risk perception and SNSs. While all users show an awareness and a recognition of the risks on SNSs, most users exhibit a lack of concern about the risks on SNSs and do not think that these negative events are likely to happen to them. While it might be expected that users would be most concerned and have highest risk perceptions for the serious threatening risks such as cyberbullying and meeting strangers, this is not the case and users express higher levels of concern about and perceive greater threats from risks to their reputation. For most of the negative events on SNSs, when compared to the other age groups, adolescents perceive themselves to be at a higher risk, show higher levels of awareness, are more concerned and perceive the consequences of risks to be higher. The qualitative interviews and focus group discussions highlight some misconceptions with regard to these risks and in particular users’ lack of awareness of the scale and scope of the audience on SNSs and how easily their personal information can be accessed and harvested. This research examines why some users perceive themselves to be at high personal risk on SNSs and others do not. Three factors are significant predictors of the likelihood of high personal risk perceptions: prior experience of the risk, concern about the risk and age group. The most significant predictor of high personal risk perception is prior experience. Although suggested as significant predictors of risk perception by previous research, both knowledge of risk and controllability of risk show small effects on the likelihood of high personal risk perceptions. Again, contrary to the findings of previous risk perception studies, gender does not emerge as a significant predictor for any of the risk categories. This study highlights a number of behaviours on SNSs that could make users more vulnerable to risk. Users tend to underestimate the amount of time they spend on SNSs and may be unaware of the distracting aspects of SNSs. In contrast to some previous studies, this study has found that the majority of respondents have restricted their privacy settings, indicating that SNS users may be becoming more aware and concerned about the privacy risks on SNSs. However, similar to the findings of other studies, this concern does not extend to restricting the amount of information respondents disclose. Users continue to reveal substantial amounts of personal information. Adolescents are less likely than the other age cohorts studied to reveal personal contact information, but overall older adolescents and emerging adults reveal significantly more information than the other age cohorts studied. The qualitative interviews indicate that SNS users tend to be guided by the SNS company, accepting the default privacy settings and filling in the information categories provided on the SNS. To date, most studies have addressed the prevalence of these risks for children and adolescents. This study differs as it examines the prevalence of risks over a number of age cohorts and highlights that many of these risks have been experienced by emerging adults and adults. This study addresses a number of gaps in the extant literature and the research findings provide both a theoretical and a practical contribution to this field. The results of the research include a preliminary framework that captures the factors that influence risk perception on SNSs. The findings of this research can inform not only further studies of SNS risks, but also studies of other Internet and technology related risks.
Keywords: Computer Science, Ph.D.; Ph.D. Trinity College Dublin